Waste Management for Jordanian Industries Using Lean Management Principles - Mohammad D. AL-Tahat; Abdelrahman Mohammed Alrai (Wasit Journal of Engineering Sciences)
This paper is focused on managing waste that is generated by construction. Starting with expressing, how significant construction waste affecting project success, and then lean management principles were proven to be positively helping in keeping construction projects waste controlled. Where construction waste sources and causes were subcategorized under each main waste category that lean principles deal with. After that, adequate questionnaire was developed in order to collect data. These data were analyzed in order to determine the level of occurrence and significance for each waste type and to scientifically recommend the proper tools and techniques to deal with them, effective lean tools to be applied in Jordan according to waste sources that were determined.